2018
DOI: 10.1002/berj.3445
|View full text |Cite
|
Sign up to set email alerts
|

‘Universal’ early education: Who benefits? Patterns in take‐up of the entitlement to free early education among three‐year‐olds in England

Abstract: For over a decade, all three-year-olds in England have been entitled to a free part-time early education place. One aim of this policy is to close developmental gaps between higher-income and lowincome children. However, the success of the initiative depends on children accessing the places. Using the National Pupil Database, we examine all autumn-born four-year-olds attending in January 2011, and ask whether they started attending when first eligible, in January 2010. One in five children did not access their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…There are no significant effects of these compositional controls in our estimates.26 We have also estimated these models for all children (in the public and private sectors) and they are comparable to the results for the private sector but, if anything, slightly smaller. This is not surprising asCampbell et al (2018) have indicated that maintained settings are less likely to admit children when they become eligible during the school year (at the December and March cutoffs we study), implying that the first stage is smaller for this sector.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…There are no significant effects of these compositional controls in our estimates.26 We have also estimated these models for all children (in the public and private sectors) and they are comparable to the results for the private sector but, if anything, slightly smaller. This is not surprising asCampbell et al (2018) have indicated that maintained settings are less likely to admit children when they become eligible during the school year (at the December and March cutoffs we study), implying that the first stage is smaller for this sector.…”
supporting
confidence: 53%
“…Around half of children are provided their free place in the public sector and the other half in the private sector, with eligibility rules being the same across both sectors, although (Campbell et al 2018) show that in practice private sector settings are more willing to accommodate new children in January (and likely in April too). In this paper we focus on the private sector to be able to exploit its wider variation in the quality measures we use.…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…However, Campbell et al (2018) suggest that subsidies for early education are concentrated disproportionately on children who least need a head start. Coupling this with new 15/30 hours funding resulting in a shortfall for providers, there is a fear that the current context may be in fact widening inequalities, in direct contrast to stated policy aims.…”
Section: The Current Era Of Austeritymentioning
confidence: 99%
“…However, since the expansion to 30 hours, there have been a number of problems for all early years providers, including nursery schools. One concern raised in research has been the potential for the policy to result in widening inequalities, given variations in take-up by different social groups (Campbell, Gambaro, and Stewart 2018;Stewart and Waldfogel 2017). The 'free hours' system is an example of 'policy incoherence', argue Lewis and West, because disadvantaged children are less likely to 'experience the social mixing that has been shown to result in better outcomes' and also 'more often experience the poorer quality provision offered by PVI providers ' (2017, 343).…”
Section: The 15/30 Hours Policymentioning
confidence: 99%